Assessing the Prefernces of Animal Protien among Ghanaians: A Case Study in Jaman North and South District in Brong-Ahafo Region of Ghana - Patience, Kyei (Advances in Social Sciences Research Journal, 2014)
This research was aimed at assessing the preferences of animal protein among the people of Jaman North and South District in the Brong Ahafo Region of Ghana. The specific objectives were to examine the preferences of animal protein among the people of Jaman, factors that influence the choice of animal protein they make, knowledge about animal protein and the health implications associated with it. A sample of one hundred and fifty (150) respondents comprising teachers, mothers, nurses, farmers and the aged were selected from the selected towns and villages used for the study. The methodology involved field work, questionnaire, interview and survey. The results revealed that, the consumption of meat is high whiles consumption of fish is low in the districts. The people are also ignorant about the health implication associated with high intake of meat. Diet related diseases are common in the district. The result again revealed that, high consumption of meat does not only affect the health of the people but the environment as well. The study recommended that awareness creation should be made through education by home economic teachers, health professionals and nutritionist in the district. The preference of animal protein by the settlers of Jaman District has served as a basis for possible further research on the subject matter.